2017
DOI: 10.1093/ndt/gfx031
|View full text |Cite
|
Sign up to set email alerts
|

Whole-exome sequencing for prenatal diagnosis of fetuses with congenital anomalies of the kidney and urinary tract

Abstract: Applying WES to the prenatal diagnostic approach in CAKUT fetuses with or without other anomalies allows for an accurate and early etiology-based diagnosis and improved clinical management. To expedite interpretation of the results, trio sequencing should be employed; however, interpretation may nevertheless be compromised by incomplete coverage of all relevant genes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
46
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 32 publications
4
46
0
1
Order By: Relevance
“…To date, only one recent study applying exome sequencing for CAKUT cases prenatally detected a HNF1B frameshift variant. 55 In conclusion, similar to previous studies, our study indicated no differences in the prenatal renal phenotypic spectrum between intragenic HNF1B aberrations and 17q12DS, and a wide range of postnatal renal and extra-renal abnormalities for both. The most prominent postnatal phenotypic differences, potentially affecting prenatal decision making, are a more severe progress of renal impairment in individuals with intragenic HNF1B variants and the increased NDD risk, which is a confirmed feature in 17q12DS and suspected in HNF1B…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…To date, only one recent study applying exome sequencing for CAKUT cases prenatally detected a HNF1B frameshift variant. 55 In conclusion, similar to previous studies, our study indicated no differences in the prenatal renal phenotypic spectrum between intragenic HNF1B aberrations and 17q12DS, and a wide range of postnatal renal and extra-renal abnormalities for both. The most prominent postnatal phenotypic differences, potentially affecting prenatal decision making, are a more severe progress of renal impairment in individuals with intragenic HNF1B variants and the increased NDD risk, which is a confirmed feature in 17q12DS and suspected in HNF1B…”
Section: Discussionsupporting
confidence: 91%
“…To date, only one recent study applying exome sequencing for CAKUT cases prenatally detected a HNF1B frameshift variant . Likewise, the herein reported prenatal identification of an intragenic HNF1B variant in individual I1 is likely a consequence of increased availability and demand for such NGS‐based techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Until now, only 18 fetuses with confirmed disease-causing variations in BBS genes have been reported. 20,[25][26][27][28][29][30][31] Most of the clinical signs found in the fetuses and neonates (polydactyly, renal cysts, hepatic fibrosis without bile duct proliferation and situs inversus) overlap with other ciliopathies. This was confirmed by the report of 10 fetuses referred for "Meckel-like cystic kidneys" mutated in 4 BBS genes (BBS2, BBS4 BBS6 and BBS10).…”
Section: Introductionmentioning
confidence: 99%
“…Another paper on application of WES to CAKUT in the setting of normal CMA showed a detection rate of 2/22 (9.1%) for isolated CAKUT and 2/8 (25%) for CAKUT with other abnormalities. However, larger studies are needed to determine the utility of WES when applied to prenatal CAKUT . Serial ultrasonography for fetal surveillance is often utilized, while the approach to antenatal testing and timing of delivery requires individualization.…”
Section: Approach To Evaluationmentioning
confidence: 99%
“…However, larger studies are needed to determine the utility of WES when applied to prenatal CAKUT. 73 Serial ultrasonography for fetal surveillance is often utilized, while the approach to antenatal testing and timing of delivery requires individualization.…”
Section: Approach To Evaluationmentioning
confidence: 99%